Irrigation control system design for paddy field by means of internet of things. Issue 1 (January 2021) - Khairuman,; Satria, E; Anugreni, F; Asmaidi,; Rusnanda, R; Barus, E S; Yuna, A; Arifa, M
Abstract: During this time the control of the water level that is done is still using manual tools in the form of floodgates placed between rice fields and irrigation. Given the importance of controlling and monitoring the level of irrigation water in rice fields, the authors get the idea to create a control system to close the irrigation floodgates on rice fields for farmers. In addition to notification in the form of a SMS (Short Message Service) reply to the telegram application, the open and close irrigation door system in paddy fields is a major alternative that is very useful for farmers to prevent crop failures if the water in the paddy fields exceeds the limit. In this system utilizing the work of ultrasonic sensors to measure any changes in water level in the paddy fields, then the data will be received and processed in the nodemcu and water level notifications will be sent to the telegram, to drive the irrigation door on the paddy using a servo motor that will open and close the irrigation door on rice fields automatically according to the conditions specified. if the water level is <2 cm, the irrigation door will open, the buzzer will not sound. And if the water level below> 2 cm, the irrigation door will be closed, the buzzer will sound as a sign that the water needs in the field are sufficient. While the notification in the form of an sms will be sent to the telegram.